Budget-Based Performance Evaluation Of Regional Apparatus At The Tenggarong Seberang Sub-District Office - Harun, Harun; Idris, Adam; Daryono, Daryono (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2026)
This study evaluates budget and financial realization performance at the Tenggarong Seberang Sub-district Office by comparing actual outcomes with planned targets and identifying supporting and inhibiting factors. A qualitative descriptive approach with purposive sampling was applied using an evaluation framework covering objectives, inputs, activities, outputs, and outcomes. The results show that output achievement and budget absorption exceeded 90% in 2023–2024. Based on these indicators output realization relative to targets and budget absorption rates performance can be considered operationally effective and efficient. However, this effectiveness is limited, as budget allocation is not fully aligned with priority programs, and planning and implementation remain inconsistent. Supporting factors include regulations, leadership commitment, competent human resources, budget and data availability, and organizational culture. Inhibiting factors involve limited staff understanding, weak leadership follow-up, budget constraints, inappropriate performance indicators, and poor coordination. Overall, while efficiency is evident in short-term indicators, weaknesses in planning and alignment reduce overall performance quality.